Collagenous gastritis. Issue 5 (22nd October 2012) - Jin, Xiaoyi; Koike, Tomoyuki; Chiba, Takashi; Kondo, Yutaka; Ara, Nobuyuki; Uno, Kaname; Asano, Naoki; Iijima, Katsunori; Imatani, Akira; Watanabe, Mika; Shirane, Akio; Shimosegawa, Tooru
Abstract : In the present paper, we report a case of rare collagenous gastritis. The patient was a 25‐year‐old man who had experienced nausea, abdominal distention and epigastralgia since 2005. Esophagogastroduodenoscopy (EGD) carried out at initial examination by the patient's local doctor revealed an extensively discolored depression from the upper gastric body to the lower gastric body, mainly including the greater curvature, accompanied by residual mucosa with multiple islands and nodularity with a cobblestone appearance. Initial biopsies sampled from the nodules and accompanying atrophic mucosa were diagnosed as chronic gastritis. In August, 2011, the patient was referred to Tohoku University Hospital for observation and treatment. EGD at our hospital showed the same findings as those by the patient's local doctor. Pathological findings included a membranous collagen band in the superficial layer area of the gastric mucosa, which led to a diagnosis of collagenous gastritis. Collagenous gastritis is an extremely rare disease, but it is important to recognize its characteristic endoscopic findings to make a diagnosis.